A evolução da internet - KAI, Huang Pei (004, 2005)
Este trabalho trata do assunto sobre Internet, com esse trabalho apresentarei a história, como também, os avanços tecnológicos, especificamente na perspectiva da Internet, e mais sobre a segurança da Internet.
The evolution of the internet
This work deals with the matter on Internet, with that work it introduces her recounts. Treats also, of the technological advancements, specifically in the perspective of the Internet, and more on safety of the internet.
Keywords: Internet; Informação - segurança; Informação e Comunicação